Change Management: The People Dimension of Change - Strenitzerova, Mariana (Communications - Scientific letters of the University of Zilina, 2004)
Change management is the process, tools and techniques to effectively manage people and the associated human resource issues that surface when implementing business changes. Change management as a field of study finds its roots in two areas: business process improvement and psychology. The ADKAR model for change management as the diagnostic tool helps employees understand where they are in the change process. A manager can use this tool to identify gaps in his change management process and to provide effective coaching for his employees.